Uncovertebral and facet joint dislocations in cervical articular pillar fractures: CT evaluation. - Yetkin, Z; Osborn, A G; Giles, D S; Haughton, V M (American Journal of Neuroradiology, 1985)
Computed tomographic (CT) scans and plain radiographs of 21 patients with surgically treated fractures or dislocations of the cervical spine were reviewed. CT effectively demonstrated the locked or perched facets and half of the 13 articular pillar fractures. The fracture lines through the articular pillar were difficult to detect in some cases or to distinguish from a facet joint in others. However, distraction of an adjacent uncovertebral or facet joint was demonstrated by CT in each case of articular pillar fracture or locked or perched facet. Therefore, CT demonstration of a distracted facet or uncovertebral joint is an indirect sign of an unstable fracture or of a dislocation that may be more readily recognized on plain radiographs or pluridirectional tomograms.